Causal relationships of lifestyle behaviours and body fat distribution on diabetic microvascular complications: a Mendelian randomization study - Guo, Nuojin; Shi, Hekai; Zhao, Hongmei; Abuduani, Yierfan; Chen, Da; Chen, Xishuang; Wang, Hua; Li, Peicheng (Frontiers in Genetics, 2024)
Objectives: ToWe conducted this Mendelian Randomization (MR) analysis to determine the causal correlations of lifestyle behaviours and body fat distribution on diabetic microvascular complications through a Mendelian Randomization (MR).Methods: Genetic variants significantly associated with lifestyle behaviours, abdominal obesity, generalized obesity and diabetic microvascular complications were extracted from the UK Biobank (UKB) and FinnGen. The inverse variance weighted (IVW) method was regarded as the primary method. The main results were presented in odds ratio (OR) per standard deviation (SD) increase, and a series of sensitivity analyses were also conducted to validate the stability of the results.Results: There was a positive causal correlation between smoking and the development of diabetic retinopathy (OR = 1.16; 95%CI: 1.04-1.30; P =0.01). All of the indicators representing abdominal obesity had a statistically significant causal association with diabetic microvascular complications. Concerning generalized obesity, there were significant causal associations of body mass index (BMI) on diabetic nephropathy (OR = 1.92; 95%CI: 1.58-2.33; P<0.001), diabetic retinopathy (OR=1.27; 95%CI: 1.15-1.40; P<0.001), and diabetic neuropathy (OR = 2.60; 95%CI: 1.95-3.45; P<0.001). Other indicators including leg fat mass (left), and arm fat mass (left) also had a significant positive causality with diabetic microvascular complications.Conclusions: Our findings suggested that smoking has a genetically causalpositive association with the development of diabetic retinopathy rather than diabetic nephropathy and diabetic neuropathy. In addition, both abdominal obesity and generalized obesity are risk factors for diabetic microvascular complications. To note, abdominal obesity represented by waist circumference (WC) is the most significant risk factor.